PENGARUH PEMBIAYAAN QORDHUL HASAN PADA KSPPS BMT BERKAH MANDIRI TERHADAP PEMBERDAYAAN USAHA MIKRO DI DESA BANJARANYAR KABUPATEN TEGAL - Purwani, Fani Erlis (Iqtishodiah: Jurnal Ekonomi dan Perbankan Syariah, 2021)
The purpose of this study is to determine the effect of Qardhul Hasan KSPPS BMT Berkah Mandiri Financing on Micro Business Empowerment in Banjaranyar Village, The population in this research are all micro business actors in Banjaranyar Village, a number of 40 people who take the financing of Qardhul Hasan in KSPPS BMT Berkah Mandiri. In this study, sampling using total sampling or census and obtained sample of research as many as 40 respondents. This research variable use two variable that is dependent variable, and independent. For the dependent variable (y) of this research is the empowerment of micro business. For the independent variavel (x) of this study is Qardhul Hasan financing. The research method used is quantitative research method. Data collection techniques by distributing questionnaires. Data analysis technique used to answer this research is simple linear regression analysis